Surface modified polythiophene/Al2O3 and polyaniline/Al2O3 nanocomposites using poly(vinyl alcohol) for the removal of heavy metal ions from water: kinetics, thermodynamic and isotherm studies - Zeynab Karimi (IWA Publishing, 2021)
In this study, polythiophene/Al2O3 (PTh/Al2O3) and polyaniline/Al2O3 (PAn/Al2O3) nanocomposites in the presence of poly(vinyl alcohol) (PVA) as the surfactant were synthesized via in situ chemical oxidative polymerization method in aqueous medium. The synthesized nanocomposites were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). Results indicated that the Al2O3 and poly(vinyl alcohol) influenced the properties of synthesized nanocomposites. The aim of this research was to investigate the sorption characteristics of polythiophene and polyaniline nanocomposites for the removal of heavy metal cations including Pb(II), Zn(II) and Cd(II) from aqueous solution. The factors that affected the adsorption equilibrium as well as the removal efficiency of the nanoadsorbents, i.e., contact time, metal ion concentration, pH and adsorption conditions were investigated in detail. From the kinetic results, it was concluded that the pseudo-second-order kinetic model was found to be the best at describing the adsorption process for Pb(II), Zn(II) and Cd(II) on PTh-PVA/Al2O3 and PAn-PVA/Al2O3. In addition, thermodynamic analysis suggests the endothermic and spontaneous nature of the present adsorption process with increased entropy on PTh-PVA/Al2O3 and PAn-PVA/Al2O3. The results suggest polythiophene, polyaniline and their nanocomposites have great potential to be used as efficient absorbent for the removal of heavy metal ions from water. Highlights Synthesis of polythiophene nanocomposites containing Al2O3.; Products were investigated in terms of morphology.; Batch adsorption experiment was performed for the removal of heavy metal ions.; pH played vital role in the removal process.; The factors that affected the adsorption equilibrium as well as the removal efficiency, i.e., contact time, metal ion concentration, pH and adsorption conditions were investigated.;